(untitled) (Journal of Computational Mathematics, 1998)
In this paper, we develop a general way to construct contact algorithms for contact dynamical systems. Such an algorithm requires the corresponding step-transition map preserve the contact structure of the underlying contact phase space. The constructions are based on the correspondence between the contact geometry of R^2n+1 and the conic symplectic one of R^2n+2 and therefore, the algorithms are derived naturally from the symplectic algorithms of Hamiltonian systems.